PENGARUH PROFITABILITAS, LEVERAGE, CASH HOLDING DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN - Sanjaya, Alvin; Ekadjaja, Agustin (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to obtain empirical evidence regarding the effect of profitability, leverage, cash holding, and capital structure on firm value in non-cyclical consumer sector mainboard companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. This study used 45 samples and 135 data from primary consumer primary companies which were selected using a purposive sampling technique. Research data was inputted and processed using the Eviews 12 program. The results showed that leverage has a negative effect on firm value and profitability, cash holding, and capital structure do not affect firm value. The implication of this research is that leverage has a negative effect on firm value as evaluated by investors.